2009
DOI: 10.1103/physrevd.80.063520
|View full text |Cite
|
Sign up to set email alerts
|

Stagflation: Bose-Einstein condensation in the early universe

Abstract: Our universe experienced the accelerated expansion at least twice; an extreme inflationary acceleration in the early universe and the recent mild acceleration. By introducing the Bose-Einstein condensation (BEC) phase of a boson field, we have been developing a unified model of dark energy (DE) and dark matter (DM) for the later mild acceleration. In this scenario, two phases of BEC (=DE) and normal gas (=DM) transform with each other through BEC phase transition. This unified model has successfully explained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 16 publications
2
77
0
Order By: Relevance
“…The critical temperature for the condensation to take place is T cr < 2πℎ 2 n 2/3 / mk B (Dalfovo et al 1999). On the other hand, cosmic evolution has the same temperature dependence, since in an adiabatic expansion process the density of a matter‐dominated Universe evolves as ρ∝ T 3/2 (Fukuyama & Morikawa 2009). Therefore, if the boson temperature is equal, for example, to the radiation temperature at z = 1000, the critical temperature for the Bose–Einstein condensation is at present T cr = 0.0027 K (Fukuyama & Morikawa 2009).…”
Section: Cosmological Dynamics Of Bose–einstein Condensatesmentioning
confidence: 99%
“…The critical temperature for the condensation to take place is T cr < 2πℎ 2 n 2/3 / mk B (Dalfovo et al 1999). On the other hand, cosmic evolution has the same temperature dependence, since in an adiabatic expansion process the density of a matter‐dominated Universe evolves as ρ∝ T 3/2 (Fukuyama & Morikawa 2009). Therefore, if the boson temperature is equal, for example, to the radiation temperature at z = 1000, the critical temperature for the Bose–Einstein condensation is at present T cr = 0.0027 K (Fukuyama & Morikawa 2009).…”
Section: Cosmological Dynamics Of Bose–einstein Condensatesmentioning
confidence: 99%
“…Nevertheless, by considering some "standard" numerical values, it will be possible to obtain a total qualitative picture of the transition. Consequently, we estimate the values of the dark matter mass and the mean velocity of the non-relativistic dark matter particles, of the order of 1 eV [19,59] and 900 km/s, respectively. According to the general analysis of the condensation process, the first phase of condensation belongs to the standard cold dark matter ( CDM) model.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above arguments, we assume the possibility that the Bose-Einstein condensation might have happened during the early stages of cosmological evolution of the universe with a temperature comparable to the critical temperature for Bose-Einstein condensation T cr ∼ 2πh 2 n 2/3 /mk B where m is the particle mass, n is the particle density, and k B is Boltzmann's constant [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium properties of Newtonian self-gravitating Bose-Einstein condensates with short-range interactions were investigated in detail in [35,36]. The study of the cosmological implications of the Bose-Einstein condensation has also become an active field of research [37][38][39][40][41][42][43][44][45][46]. In particular, in [44] it was shown that condensate dark matter effects can be seen in the CMB matter power spectrum if the mass m χ of the condensate particle lies in the range 15 meV < m χ < 700 meV, leading to a small, but perceptible, excess of power at large scales.…”
Section: Introductionmentioning
confidence: 99%